ANALYSIS OF THE EFFECT OF BUDGETING SYSTEM AND OPERATIONAL RISK ON THE FINANCIAL PERFORMANCE OF HOUSING DEVELOPER COMPANIES - Oma Nuryanto; Rukmini; Sri Laksmi Pardanawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to examine the effect of the budgeting system and operational risk on the financial performance of housing developer companies in the Solo Raya region. The research population consists of 34 companies that are members of the Real Estate Indonesia (REI) Solo Raya Chapter. Data were collected using a structured questionnaire and analyzed using multiple linear regression with SPSS. The results show that the budgeting system has a positive and significant effect on financial performance, with a significance value of 0.028 (< 0.05). Meanwhile, operational risk does not have a significant partial effect, although it contributes jointly with the budgeting system in influencing financial performance, as indicated by a significance value of 0.002 in the F-test. The coefficient of determination (Adjusted R²) is 0.299, indicating that 29.9% of the variation in financial performance can be explained by the two independent variables. These findings highlight the importance of strengthening the budgeting process and maintaining effective risk management practices in order to enhance financial performance.